Reversible chirality inversion of an AuAgx-cysteine coordination polymer by pH change - Ni, Bing; Vivod, Dustin; Avaro, Jonathan; Qi, Haoyuan; Zahn, Dirk; Wang, Xun; Cölfen, Helmut (Nature Communications, 2024)
Responsive chiral systems have attracted considerable attention, given their potential for diverse applications in biology, optoelectronics, photonics, and related fields. Here we show the reversible chirality inversion of an AuAgx-cysteine (AuAgx-cys) coordination polymer (CP) by pH changes. The polymer can be obtained by mixing HAuCl4 and AgNO3 with L-cysteine (or D-cysteine) in appropriate proportions in H2O (or other surfactant solutions). Circular dichroism (CD) spectrum is used to record the strong optical activity of the AuAg0.06-L-cys enantiomer (denoted as L0.06), which can be switched to that of the corresponding D0.06 enantiomer by alkalization (final dispersion pH > 13) and can be switched back after neutralization (final dispersion pH <8). Multiple structural changes at different pH values (≈9.6, ≈13) are observed through UV-Vis and CD spectral measurements, as well as other controlled experiments. Exploration of the CP synthesis kinetics suggests that the covalent bond formation is rapid and then the conformation of the CP materials would continuously evolve. The reaction stoichiometry investigation shows that the formation of CP materials with chirality inversion behavior requires the balancing between different coordination and polymerization processes. This study provides insights into the potential of inorganic stereochemistry in developing promising functional materials.
CRIS-Team Scopus Importer:2024-03-22